A comparative study on dietary behavior, nutritional knowledge and life stress between Korean and Chinese female high school students - Son, Sohwan; Ro, Yoona; Hyun, Hwajin; Lee, Hongmie; Song, Kyunghee (Nutrition research and practice, 2014)
Dietary behavior and life stress in adolescence is related to growth rate and learning ability. This study was conducted to identify the relations between dietary habits, dietary attitude nutritional knowledge and life stress among high school girls in Korea and China. The subjects of this study were 221 high school girls in Korea and 227 high school girls in China. The questionnaire were about dietary habits, dietary attitude, nutritional knowledge and life stress. The dietary habits of chinese girls were healthier than those of Korean girls with a significant difference (P < .001). There was no significant difference in dietary attitude between Korean girls and Chinese girls. Korean girls had more nutritional knowledge than Chinese girls with a significant difference (P < .001). Korean girls did less physical exercise but spent more time watching TV and using PCs, compared to Chinese girls. Korean girls' degree of confidence in nutrition information that they had learned and their performance in their real lives were low. Also, they had a low level of awareness of the need for nutritional education. There was no significant difference in life stress between the two groups. Dietary habits had a significantly negative correlation with life stress in both Korean and Chinese girls (P < .01, P < .001). As for Chinese students, dietary attitude had a negative correlation with life stress with a significant difference (P < .05). As for Korean girls, nutritional knowledge had a negative correlation with life stress with a significant difference (P < .05), which means as life stress was less, dietary habits were better. This study shows that effective nutrition education programs should include components that encourage application of learned nutrition information to real life, increase physical exercise and reduce life stress.